Pengaruh Makro Ekonomi Terhadap Penerimaan Pajak Dengan Ekspor Sebagai Variabel Mediasi - Rahmadani, Nabila; Oktavia, Vicky (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2024)
The aim of this study was to examine the impact of inflation, interest rates, and exchange rates on tax and export revenues while considering them as mediating variables. The research utilized secondary data, specifically a time series comprising a total of 120 data points obtained from the Ministry of Finance, Central Statistics Agency, and Bank Indonesia spanning from 2013 to 2022. The analysis involved the application of the Linear Regression method, path analysis, and Sobel test. The research findings indicate that inflation, interest rates, and exchange rates collectively affect exports. While inflation and interest rates do not influence tax revenues, exchange rates and exports do. Exports have the potential to mediate the impact of inflation on tax revenues, as evidenced by the Sobel test. However, exports cannot mediate the impact of interest rates and exchange rates on tax revenues. This study contributes to advancing the understanding of export variables as mediating factors in the determination of tax revenues.